(untitled) (Research, Society and Development, 2021)
The knowledge of the physical and flow properties of the products to be stored are essential for determining the type of flow in silos, hoppers and conveyors, enabling proper handling and processing of the product, in such a way as to obtain an economical, safe and durable structure , assuming a high interest in Brazil due to the fact that the country does not have a standard for dimensioning and designing these structures. This work sought to overcome this limitation by determining the physical and flow properties of two nationally expressive agricultural products (corn and wheat grains) that could be included in a future Brazilian standard for actions and flow in silos. To obtain the data, a direct translational shear device (TGS 70-140) and two wall surfaces were used: smooth and rough steel, as these are the materials with the greatest possibility of use in the construction of silos. The flow properties (consolidated specific gravity, instantaneous internal friction angle, effective instantaneous internal friction angle, wall friction angle and cohesion) and the physical properties (granulometry and moisture content) of the products were determined. The experimental values ​​were compared with those prescribed by the foreign standards Eurocode 1 and ISO 11697. Based on the results obtained, it is verified that the properties of both products differ from the values ​​proposed by those standards, with some parameters being overestimated in relation to those obtained experimentally . The values ​​obtained can be used as parameters for the elaboration of a silo project, equipment prediction and processing of the type of flow for the national cultivars of corn and wheat, respecting the intrinsic specificities of the national cultivars.